Clinical Studies on 1 Case of Tradive Dyskinesia by Oriental Medical Treatment - Chang-Suk, An; Chang-Kil, Yoo; Tae-Hui, Kim; Ki-Rok, Kwon; Sung-Mo, Choi (Korean Pharmacopuncture Institute, 2002)
Objective : This study was performed to evaluate the treatment of acupuncture therapy including Herbal Acupuncture in Tardive Dyskinesia. Methods & Result : We treated 1 case of Tardive Dyskinesia patient with Acupuncture and herbal Acupuncture, herbal medicine. Acupuncture therapy was taken on acupoints including CV12 (Chungwan:中脘), ST40 (Pungnyung:豊隆), SP3 (Taeback:太白). As the results of this treatments, little change of tongue motion was observed, but general conditions of the patient was improved. Conclusions : Oriental medical treatments was little effective in this disease, but general conditions of the patient was improved. We think that it need the further study and clinical trial for Tardive Dyskinesia.